2020
DOI: 10.4269/ajtmh.19-0642
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Scrub Typhus, Murine Typhus, and Spotted Fever Seropositivity in Urban Areas, Rural Plains, and Peri-Forest Hill Villages in South India: A Cross-Sectional Study

Abstract: . Scrub typhus and spotted fever group rickettsioses are thought to be common causes of febrile illness in India, whereas they rarely test for murine typhus. This cross-sectional study explored the risk factors associated with scrub typhus, tick-borne spotted fever, and murine typhus seropositivity in three different geographical settings, urban, rural, and hill villages in Tamil Nadu, South India. We enrolled 1,353 participants living in 48 clusters. The study included a questionnaire survey and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
6
31
1
Order By: Relevance
“…The two community-based studies conducted during the period in this review (2016 and 2017, respectively) showed PLOS NEGLECTED TROPICAL DISEASES seroprevalences of 40.3% and 31.8% [17,18]. A recent study among urban areas, rural plains, and peri-forest hill villages in Tamil Nadu showed a seroprevalence of 28.1% [19]. The data so far suggests that the seroprevalence of scrub typhus in the community is about 30% which is comparable to endemic infections like tuberculosis in India, which has an estimated prevalence (latent tuberculosis) of 40% [20].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 67%
“…The two community-based studies conducted during the period in this review (2016 and 2017, respectively) showed PLOS NEGLECTED TROPICAL DISEASES seroprevalences of 40.3% and 31.8% [17,18]. A recent study among urban areas, rural plains, and peri-forest hill villages in Tamil Nadu showed a seroprevalence of 28.1% [19]. The data so far suggests that the seroprevalence of scrub typhus in the community is about 30% which is comparable to endemic infections like tuberculosis in India, which has an estimated prevalence (latent tuberculosis) of 40% [20].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 67%
“…We have previously shown that the IgG response to scrub typhus infection in those with low initial IgG antibody levels was less pronounced and persistent compared to those with initially high IgG levels [ 14 ] ( Fig 1B ). This, together with the strong increase in IgG sero-positivity with age typically found in scrub typhus [ 11 , 12 ] ( Fig 1C ) suggests a gradual accumulation of IgG antibodies after multiple infections ( Fig 1D ). Similar dynamics have long been known for other infections, in particular Influenza [ 15 ].…”
Section: Introductionmentioning
confidence: 74%
“…Due to a small sample size in our previous study [ 14 ] we were unable to explore whether the observed effect was directly associated with IgG antibody levels or due to confounding by age. Older individuals are at a higher risk of severe scrub typhus [ 4 ] and are also known to have higher levels of scrub typhus IgG ( Fig 1C ) [ 11 , 12 ]. We therefore retrospectively enrolled additional scrub typhus cases to investigate the association between initial IgG antibody levels and severe infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations